Analysis of Individual Efforts, Organizations, Work Environments with Burnout Syndrome Based on Theory Maslach on Infection Room Nurses - Mudayatin, Lilik; Sajidin, Muhammad; Azizah, Lilik Ma'rifatul; Lestari, Indah; Maryam, Dewi; Zamroni, Asroful Hulam (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurses who care for patients with infectious diseases have a high risk of exposure to contagion which causes high levels of stress and tension in nurses. Management has made efforts to pay attention to the quality of life of nurses in infectious disease installations, but nurses are still found to experience Burnout Syndrome due to high workloads, less efficient organizational systems regarding schedules and teams in shifts, and an unsupportive work environment. This research aims to analyze the factors of individual, organizational, and work environment efforts toward Burnout Syndrome in infectious disease installations. Method: This research used a cross-section design with a sample of 1406 nurses at RSUD Dr. Soetomo. This research used a purposive sampling technique, namely infectious disease installation nurses with the criteria of being an executive nurse and not being on leave. Data collection using a questionnaire includes independent variables in the form of individual effort, organization and work environment as well as the dependent variable in the form of Burnout Syndrome with validity and reliability tests in the form of a person correlation value of <0.5 and a Cronbach's alpha value of 0.729 >0.6. Data were analyzed using logistic regression with a p-value ≤ 0.05. Results: The research results show that individual effort (0.018), organizational effort (0.032), and work environment effort (0.006) have a significant relationship with nurse burnout syndrome. Conclusion: Good individual, organizational, and environmental efforts have an impact on preventing burnout in nurses. This makes infectious disease nurses, even with a high workload and risk of exposure, have low Burnout Syndrome because they have good coping, a supportive organizational atmosphere, and a comfortable physical environment.